Community of Plants for Traditional Medicine in Kerandangan Natural Tourism Park West Lombok - Nanisfi, Maulidatin; Santoso, Didik; Japa, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The development of modern medicine, with its various advantages and disadvantages, has eroded people's knowledge about the use of traditional medicine. Thus, it is important to conduct research on the use of natural resources (plants) as traditional medicine by the community. This application used a qualitative method, with observation and interviews to obtain in-depth information about the behavior of the Kerandangan Hamlet Community in utilizing plants as traditional medicine. The results showed that the local community of Kerandangan still uses traditional medicine from surrounding plants that have been taught from generation to generation to cure various diseases. Various species, families, and parts of plants were used by the community of Kerandangan as traditional medicine. Finally, the level of diversity of medicinal plant species was found to in a moderate level.